Act of Ambivalence and Resistance, Cricket and Colonialism, Politics of Self and Other, Indian Pluralism, Anti-colonial Propaganda, Oppressive Schooling System, Hybridity, Centre/Periphery and Master/Slave Dichotomy with Reference to R. K. Narayan’s Swami - Mandal, Partha Sarathi (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Narayan’s Swami and Friends (1935) luminously portrays its child protagonist Swaminathan’s adventures in soul making, his skirmishes with his little comrades and reconciliations in his soupy school, his contact with the experienced adult world vis-à-vis apparently apolitical, shallow and banal Swami and Friends (1935) also postulates encoded political and cultural resistance so strategically camouflaged by Narayan’s narrative devise. Narayan’s Anti-colonial propaganda, his aversion to fundamentalism and authoritarianism, his earnest desire to bring the subaltern narrative into our mainstream narrative give him a special place in literary world. Kudos to the Nietzschean Will to Power of the common inhabitants of Malgudi and the little urchins of Albert Mission School that they dared to join the protest march against the hegemony of their white colonial masters. Swami much like Ishaan of Aamir Khan’s Taare Zameen Par (2007) used to shudder at the very thought of his monotonous school where his wings of freedom used to be crushed under the fatal mill of the authoritarian and strict teachers except D.Pillai who was famous among the students. Swaminathan’s hybrid identity, Rajam’s Europeanized existence, overlapping associations of tradition and modernity, class struggle, Centre/Periphery, Self/Other, Master/Slave dichotomy in Swami and Friends (1935) actually celebrate Narayan’s deep concern for our pluralistic and multicultural Indian identity where Narayan has also given space to the subaltern existence like Rajam’s family cook who was insulted and undervalued by Rajam only because Rajam belonged to the centre of a power structure. In this paper I would like to investigate in which way Narayan has pointed out the various agathokakological entities of human life through the artistic representation of his characters, his celebration of India’s heterogeneous identity, class struggle, the marginalized and peripheralized existence of subaltern voices, politics of colonial masters’ Self and the muted Other in an unequal power structure where a very limited number of people actually get access to the resources , ambivalence, hybrid identity etc. with reference to Swami and Friends (1935).